Pancreatic Neuroendocrine Tumor in the Setting of Dorsal Agenesis of the Pancreas - Samih Nassif; Cecilia Ponchiardi; Teviah Sachs (Case Reports in Gastrointestinal Medicine)
Dorsal agenesis of the pancreas (DAP) is an uncommon embryological abnormality where there is absence of the distal pancreas. DAP is mostly asymptomatic, but common presenting symptoms include diabetes mellitus, abdominal pain, pancreatitis, enlarged pancreatic head, and, in a few cases, polysplenia. MRCP and ERCP are the gold standard imaging techniques to demonstrate the absence of the dorsal pancreatic duct. The literature on the association of pancreatic neoplasia and DAP is limited. We present the case of a pancreatic neuroendocrine tumor in a patient with dorsal agenesis of the pancreas, with a review of the related literature.